Effect of silicon application on the germination of pepper seeds under salt stress (Research, Society and Development, 2020)
The aim of the present study was to evaluate the germination of Naga Jolokia seeds (Capsicum chinense Jacq.) Under salt stress with the effect of applying silicon doses. The experimental design used was entirely random, with nine treatments (doses of NaCl associated with Silicon) and four replications, consisting of 36 experimental units. For salt stress, sodium chloride concentrations were used at doses of 0; 3.5 and 4.5 dS m-1, and silicon dioxide was used as the source of silicon, with the following doses being applied: 0, 30 and 60 g of silicon 100 kg seeds-1. The analyzes performed were abnormal seedlings, dead seedlings, germination, germination speed index, shoot and root length and fresh and dry mass. The results of the analysis of variance showed a significant difference for treatments (P>0.05), for abnormal seedlings, dead seedlings, germination, emergence speed index and seedling dry mass, indicating a positive effect of silicon application, concluding that conditions of high salinity, negatively influence the observed variables, however, in treatments with salinity the addition of silicon helps to attenuate the stress in the plant.